2019
DOI: 10.2169/internalmedicine.1549-18
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib Confers a Progression-free Survival in a Patient with Ewing's Sarcoma/Primitive Neuroectodermal Tumor of the Lung

Abstract: Ewing's sarcoma (ES)/primitive neuroectodermal tumors (PNETs) are highly malignant neoplasms that usually affect the bones and soft tissues in children and young adults. ES/PNET of the lung is very rare and is associated with a poor prognosis. We herein report a case of ES/PNET of the left lung in a 45-year-old man. He was treated with neoadjuvant chemotherapy and pneumonectomy, but unfortunately his disease recurred 1.5 months after surgery. He was started on pazopanib, which resulted in a five-month progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…PET-CT of Ewing’s sarcoma in lung often presents with large volume, smooth margins, and high fluorodeoxyglucose uptake, SUV MAX10-30.3. In addition, fluorodeoxyglucose positron emission tomography (PET) can help to rule out the possibility of pulmonary metastasis by extra-pulmonary Ewing’s sarcoma ( 4 , 6 8 , 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET-CT of Ewing’s sarcoma in lung often presents with large volume, smooth margins, and high fluorodeoxyglucose uptake, SUV MAX10-30.3. In addition, fluorodeoxyglucose positron emission tomography (PET) can help to rule out the possibility of pulmonary metastasis by extra-pulmonary Ewing’s sarcoma ( 4 , 6 8 , 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that anlotinib and pazopanib have been used in the treatment of PPES and achieve incredible results,but are not considered standard treatment ( 4 , 8 ). Takigami reported that a case of PPES received neoadjuvant chemotherapy and total pneumonectomy, recurred 1.5 months after surgery, and achieved a progression-free survival of 5 months after taking pazopanib ( 4 ). Zhang reported that a case of PPES received 5 cycles of chemotherapy, but he did not benefit unambiguously.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TP53 testing is necessary, and if possible, radiotherapy and genotoxic chemotherapy should be avoided in carriers. Recent studies have shown that tumor angiogenesis can promote the growth and metastasis of solid tumors, and anlotinib and pazopanib have been reported to be effective in the treatment of PPES, but they are not considered standard treatment 6,8 . Anlotinib was selected for subsequent treatment after multidisciplinary discussion.…”
Section: Discussionmentioning
confidence: 99%
“…PPES is rare, and the clinical symptoms of cough, phlegm, chest pain, hemoptysis or fatigue, etc are nonspecific. The disease has been found to occur at any age, mostly in children and adolescents, and peaks at the age of 20–30 years old, without any difference in gender 5–7 …”
Section: Discussionmentioning
confidence: 99%
“…Regimens of VAC/IE or VDC/IE are commonly used in chemotherapy, but their chemotherapeutic effects are not always satisfactory. Takigami et al[12] reported on a lung PNET case that had been treated with VDC/IE chemotherapy for 5 mo before surgery; after the tumor was resected, it recurred 1.5 mo later. In this case, adriamycin was replaced with actinomycin-D due to a cumulative dose of doxorubicin near 500 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%